2012
DOI: 10.1097/aln.0b013e3182426ed6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Preoperative E/e′ Ratio in Patients with Off-pump Coronary Artery Surgery

Abstract: Increased LV filling pressure, assessed by E/e' ratio, is an independent predictor of 30-day and 1-yr MACE in patients who undergo elective off-pump coronary artery bypass graft surgery. These findings indicate that measurements of E/e' may assist in preoperative risk stratification of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…It is also reported that additional information such as brain natriuretic peptide (BNP) level, echo‐blood flow Doppler, echo‐derived parameters, or the presence of atrial fibrillation are needed for the diagnosis of diastolic LV failure in patients with E/E' ratio of > 8 but < 15, even in those with normal LV systolic function . Thus, the use of a cutoff value for E/E' ratio of > 15 is reasonable to define LV diastolic dysfunction . In the present study, we set three categories of E/E' ratio of < 8, 8–15, and ≥ 15.…”
Section: Discussionmentioning
confidence: 97%
“…It is also reported that additional information such as brain natriuretic peptide (BNP) level, echo‐blood flow Doppler, echo‐derived parameters, or the presence of atrial fibrillation are needed for the diagnosis of diastolic LV failure in patients with E/E' ratio of > 8 but < 15, even in those with normal LV systolic function . Thus, the use of a cutoff value for E/E' ratio of > 15 is reasonable to define LV diastolic dysfunction . In the present study, we set three categories of E/E' ratio of < 8, 8–15, and ≥ 15.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated E / e ′ ratio (>15) is the best Doppler predictor of increased mean LV diastolic pressure and pulmonary artery wedge pressure. Recently, Lee et al . reported the prognostic impact of preoperative E / e ′ ratio in patients who underwent off‐pump coronary artery surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that 50% of heart failure patients have normal systolic left ventricular (LV) function, and diastolic dysfunction has been suggested as the cause of heart failure in this patient population, particularly in aged individuals . Patients with LV diastolic dysfunction are prone to develop pulmonary edema and MACE owing to diminished LV compliance due to any cause . With the advancement in anesthesia and surgical techniques, the average age of the patients for whom surgical operations are performed has increased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were anesthetized following our institution's perioperative anesthesia management strategies for OPCAB surgery, and which were previously described in detail in another study [13]. All patients were induced anesthesia with an intravenous (IV) injection of 0.2 mg/kg etomidate and continuous infusion of propofol and remifentanil using a target control infusion (TCI) pump (Orchestra® Base Prima; Fresenius Kabi, Brezins, France).…”
Section: Methodsmentioning
confidence: 99%